Mini Review: Antimicrobial Control of Chlamydial Infections in Animals: Current Practices and Issues - Bommana, Sankhya; Polkinghorne, Adam (Frontiers in Microbiology, 2019)
Chlamydia are a genus of successful obligate intracellular pathogens spread across humans, wildlife and domesticated animals. The most common species reported in livestock in this genus are Chlamydia abortus, Chlamydia psittaci, Chlamydia suis and Chlamydia pecorum. Chlamydial infections trigger a series of inflammatory disease-related sequelae including arthritis, conjunctivitis, pneumonia and abortion. Other bacteria in the phylum Chlamydiae have also been reported in livestock and wildlife but their impact on animal health is less clear. Control of chlamydial infections relies on the use of macrolides, fluoroquinolones and tetracyclines. Tetracycline resistance (TETR) reported for porcine C. suis strains in association with the use of tetracycline feed is a potentially significant concern given experimental evidence highlighting that the genetic elements inferring TETR may be horizontally transferred to other chlamydial species. As documented in human Chlamydia trachomatis infections, relapse of infections, bacterial shedding post-antibiotic treatment and disease progression despite chlamydial clearance in animals have also been reported. The identification of novel chlamydiae as well as new animal hosts for previously described chlamydial pathogens should place a renewed emphasis on basic in vivo studies to demonstrate the efficacy of existing and new antimicrobial treatment regimes. Building on recent reviews of antimicrobials limited to C. trachomatis and C. suis, this review will explore the use of antimicrobials, the evidence and factors that influence the treatment failure of chlamydial infections in animals and the future directions in the control of these important veterinary pathogens.